The Human Resource Contribution for Organizations Growth: Leveraging HR for Organizational Growth (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The challenge of growth faces most companies in today’s highly interdependent, competitive global economy. HR is staring at an incredible opportunity to increase its impact on organizational performance and become a true strategic partner by contributing to the organization and work design challenges that enable growth. This is an important focus for HR, because talent management is inextricably linked to organization and work systems design, in a way that each constrains the other. By expanding its focus to include organization and work design, HR multiplies its influence on both people and business performance. Growth agendas present a compelling need for this expanded HR contribution. Whether seeking organic growth in new markets, expanding through developing innovative products, services, and business models, or growing through acquisitions and partnerships, companies face the need to find and integrate new resources, realign existing ones, and reconfigure core design features to handle the increased size and complexity that accompanies rapid growth. Various growth scenarios present different challenges. Thus, gaining organization design expertise and leadership is no easy task, but it can make an appreciable difference in organization effectiveness.